Making sense of organisational conflict: An empirical study of enacted sensemaking in everyday conflict at work - Elisabeth Naima Mikkelsen (Copenhagen Business School (CBS), 2012)
This study is about everyday conflicts that occur at work; how meaning and action interact in processes of conflict handling in organisational conflicts that arise naturally in every arena of daily life when people meet in social interactions. I approach the phenomenon of conflict by exploring those social processes of organisational sensemaking that arise when conflict occurs in a nonprofit organisation, my own processes of sensemaking of the research process about conflict, and conflict research literature's sensemaking of the concept of conflict. Weick argues that “[t]he basic idea of sensemaking is that reality is an ongoing accomplishment that emerges from efforts to create order and make retrospective sense of what occurs” (1993, p. 653). Accordingly, sensemaking is conceptualised as a process of social construction where individuals attempt to interpret and explain sets of cues, or signals from their environments. The term can also be applied to the craft of research as sensemaking, in which researchers as sensemakers actively analyse the empirical material and generate representations of how reality is (Weick, 1989). Accordingly, in this study, I basically aim to understand conflict at work and understand research about conflict at work; that is, how conflict, as a social phenomenon, plays out in organisational cultures and group dynamics, and how conflict is conceptualised in conflict research literature. The study examines the following research questions from a sensemaking perspective: 1) How is conflict conceptualized in conflict research literature? 2) How do staff and management experience and act out conflicts in the nonprofit organisation of NGO Plus and how does changing conflict sensemaking affect conflicts at work? 3) What is my process of theorizing in conflict research?
hdl:10398/8609
Keywords: 650